Integrated transcriptome and metabolome analyses reveal key genes regulating jujuboside biosynthesis in Ziziphus jujuba var. spinosa - Geng, Dali; Yang, Xiaozhou; Wang, Xinhong; Chi, Xiaojun; Tang, Xiaohan; Ma, Xiaojun; Li, Xuexiang; Pu, Menglin; Shu, Jing (Frontiers in Plant Science, 2026)
The seeds of Ziziphus jujuba var. spinosa are a traditional Chinese medicine for treating insomnia, with jujuboside A and jujuboside B as their core bioactive components. However, the biosynthetic pathways and regulatory mechanisms of these triterpenoid saponins remain poorly understood. In this study, we investigated the accumulation patterns of jujube saponins across 10 varieties at 45, 65, and 85 days after flowering (DAF). Integrated transcriptomic and metabolomic analyses revealed 2,040 differentially expressed genes (DEGs) and 1,593 differentially accumulated metabolites (DAMs). Among these, 35 core DEGs were consistently significant across comparisons, enriched in saponin metabolism, monooxygenase activity, and glycosylation processes. A Uridine Diphosphate (UDP)-glucosyltransferase and two CYP450 family members exhibited expression patterns positively correlated with saponin accumulation, showing upregulation during 45 and 65 DAF and suppression by 85 DAF. qRT-PCR validation confirmed their higher expression in high-saponin varieties. Additionally, downregulated stress–response genes in high-saponin varieties suggested a potential link between abiotic stress tolerance and enhanced saponin production. These findings identify key glycosyltransferase and cytochrome P450 genes potentially governing jujuboside biosynthesis, providing critical insights for metabolic engineering and quality improvement of Z. jujuba.